Nadzór nad radami narodowymi, organami samorządu mieszkańców i terenowymi organami administracji w świetle nowych przepisów - Leoński, Zbigniew (Wydział Prawa i Administracji UAM, 1984)
The Peoples' Councils and Local Self-Government System Act of 20 July 1983 introduced certain new elements to local administration system. Treating people's councils as organs of local self-government was one of those elements. People's councils and organs of municipal and rural residents self-government are handled in the new regulation as parts of the same organizational structure (of local self- -government system). It resulted in an increase of weight of decentralization and supervision problems in aspect of local administration. The present article contains a study of regulation pertaining to supervision excercised in three systems: 1. supervision performed upon people's councils, 2. supervision upon organs of municipal and rural self-government and 3. supervision upon administrative organs of people's councils. In the first system, supervision is performed by the Council of State (upon all councils in principle) and by voivodship (district) councils upon municipal, quarter, and rural district councils. The supervision covers control of legality of decisions and corrective means which cannot violate a principle of independence in activities. The newly introduced obligation of lending assistance to supervised organs is characteristic for a socialist state. The Polish Seym (Diet) is also obliged by the Act to take care of self-government charakter of people's councils, special means are provided for the Council of State to be used in instances of violating independence of people's councils by other organs. Supervision of rural self-government organs is trusted to rural district council and to its presidium, while supervision upon municipal self-government organs is performed by municipal (quarter) council and its presidium. Means of control are not intensive there but also the scope of affairs relegated to that self government is not substantial at least as far as decisional competence is concerned. In practice, the supervision upon organs of administration of people's councils is of a crucial importance, as those are implementing tasks of people's councils. On the central level, the supervision is divided onto various organs: Council of Ministers, Prime Minister, Minister of Administration and Region-Shaping Economy and branch ministers, what can threaten with inconsistencies in performing that function. On the voivodship level, the supervision is performed by voivodes and heads of departments of voivodship administration upon relevant organs of administration on the level of rural district, city, quarter. Yet, competence of higher level organs is differentiated subject to tasks performed by local organs of administration. In the decentralised sphere (when organs of administration act as executive organs of people's councils), means of exercised influence are those of supervision. But if those organs act in the sphere excluded from the competence of people's councils, the means are close to hierarchical subordination. That latter influence is named governance in the Act. The differentiated influence is effected by a dual role of local organs of administration since a dualistic model of local administration (self- -governmental and governmental) is rejected in the Act.
Supervision on people's councils, residents' self-government and local organs of administration in light of the new regulation